Postoperative red blood cell distribution width predicts functional outcome in aneurysmal subarachnoid hemorrhage after surgical clipping: A single-center retrospective study - Zhao, Long; Zhang, Yi; Lin, Ping; Li, Weida; Huang, Xingyuan; Li, Hangyang; Xia, Mingkai; Chen, Xinlong; Zhu, Xi; Tang, Xiaoping (Frontiers in Neurology, 2022)
Objective Red blood cell (RBC) parameters are associated with outcomes following aneurysmal subarachnoid hemorrhage (aSAH), but their predictive value remains uncertain. This study aimed to detect the association between RBC parameters and functional outcome in aSAH patients undergoing surgical clipping. Methods This retrospective observational study included aSAH patients who underwent surgical clipping at Affiliated Hospital of North Sichuan Medical College between August 2016 and September 2019. The functional outcome following aSAH was assessed by modified Rankin Scale (mRS), and mRS 3–6 was defined as poor functional outcome. Results Out of 187 aSAH patients included (62% female, 51–66 years old), 73 patients had poor functional outcome. Multivariate logistic regression of admission parameters showed that World Federation of Neurosurgical Societies (WFNS) grade (odds ratio [95% CI]: 1.322 [1.023–1.707], p = 0.033) and white blood cell (WBC) (odds ratio [95% CI]: 1.136 [1.044–1.236], p = 0.003) were independently associated with poor functional outcome. In postoperative parameters, RBC distribution width (RDW) (odds ratio [95% CI]: 1.411 [1.095–1.818], p = 0.008), mean platelet volume (MPV, odds ratio [95% CI]: 1.253 [1.012–1.552], p = 0.039) and admission WFNS grade (odds ratio [95% CI]: 1.439 [1.119–1.850], p = 0.005) were independently associated with poor functional outcome. The predictive model including WFNS grade, admission WBC, and postoperative RDW and MPV had significantly higher predictive power compared to WFNS grade alone (0.787 [0.722–0.852] vs. 0.707 [0.630–0.784], p = 0.024). The combination of WFNS grade and WBC on admission showed the highest positive predictive value (75.5%) and postoperative RDW and MPV combined with admission WFNS grade and WBC showed the highest negative predictive value (83.7%). Conclusion Postoperative RDW is independently associated with poor functional outcome in aSAH patients undergoing surgical clipping. A combined model containing postoperative RDW may help predict good outcome in patients with aSAH after timely aneurysm clipping.